Extracellular Nucleic Acids - Kikuchi, Yo.; Rykova, Elena Y.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Extracellular nucleic acids have recently emerged as important players in the fields of biology and the medical sciences. In the last several years, extracellular nucleic acids have been shown to be involved in not only microbial evolution as genetic elements but also to have structural roles in bacterial communities, such as biofilms. Circulating DNA and RNA have been found in human blood and expected to be useful as non-invasive markers for the diagnosis of several diseases. In addition, extracellular nucleic acids have attracted attention as active modulators of the immune system of higher organisms, including humans. This book covers nearly all of the newly developing fields related to extracellular nucleic acids, including those of basic biology, ecology and the medical sciences, and provides readers with the latest knowledge on them.
Extracellular DNA as Matrix Component in Microbial Biofilms -- Gene Transfer Agents and Defective Bacteriophages as Sources of Extracellular Prokaryotic DNA -- Roles of Extracellular DNA in Bacterial Ecosystem -- Stable Extracellular DNA: A Novel Substrate for Genetic Engineering that Mimics Horizontal Gene Transfer in Nature -- Extracellular Nucleic Acids of the Marine Phototrophic Bacterium Rhodovulum sulfidophilum and Related Bacteria: Physiology and Biotechnology -- Systemic RNAi in C. elegans from the Viewpoint of RNA as Extracellular Signals -- Circulating Nucleic Acids in Health and Disease -- Circulating MicroRNAs in Cancer -- Biology and Diagnostic Applications of Cell-Free Fetal Nucleic Acids in Maternal Plasma -- The Biology of Circulating Nucleic Acids in Plasma and Serum (CNAPS) -- Modulation and Regulation of Gene Expression by CpG Oligonucleotides -- Immune Recognition of Nucleic Acids and Their Metabolites.
Keywords: Life sciences; Biochemistry; Cytology; Life Sciences; Cell Biology; Biochemistry, general